2015
DOI: 10.1007/s13361-015-1195-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Internal Energy Distributions of Ions Created by Electrospray Ionization and Laser Ablation-Liquid Vortex Capture/Electrospray Ionization

Abstract: Recently a number of techniques have combined laser ablation with liquid capture for mass spectrometry spot sampling and imaging applications. The newly developed noncontact liquid-vortex capture probe has been used to efficiently collect material ablated by a 355 nm UV laser in a continuous flow solvent stream in which the captured material dissolves and then undergoes electrospray ionization. This sampling and ionization approach has produced what appears to be classic electrospray ionization spectra; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…An experimentally verified imaging resolution of 0.62 μm in the analysis of phase‐separated polymers was reached, making it one of the highest spatial resolution ambient ionization MSI techniques yet reported. In addition, thermometer ion and empirical studies have shown that for small organic and biological molecules, as well as medium size proteins (e.g., bradykinin and cytochrome c , 1060 and ~12,000 Da, respectively), the LA‐LVC/ESI technique is a 'soft' ionization method despite the use of the UV laser (349 nm) . This makes the technique suitable for a wide range of biological imaging applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An experimentally verified imaging resolution of 0.62 μm in the analysis of phase‐separated polymers was reached, making it one of the highest spatial resolution ambient ionization MSI techniques yet reported. In addition, thermometer ion and empirical studies have shown that for small organic and biological molecules, as well as medium size proteins (e.g., bradykinin and cytochrome c , 1060 and ~12,000 Da, respectively), the LA‐LVC/ESI technique is a 'soft' ionization method despite the use of the UV laser (349 nm) . This makes the technique suitable for a wide range of biological imaging applications.…”
mentioning
confidence: 99%
“…In addition, thermometer ion and empirical studies have shown that for small organic and biological molecules, as well as medium size proteins (e.g., bradykinin and cytochrome c, 1060 and~12,000 Da, respectively), the LA-LVC/ESI technique is a 'soft' ionization method despite the use of the UV laser (349 nm). [18] This makes the technique suitable for a wide range of biological imaging applications.…”
mentioning
confidence: 99%
“…Using a 355 nm laser with 10 Hz repetition frequency and 7 ns pulse width, profiling of stamped ink and a selected lipid in mouse brain tissue resulted in imaging resolutions of 6 and 50 μm, respectively. Despite the utility of an UV laser, LA‐LVC/ESI has been demonstrated to be a “soft” technique, yielding mass spectra of bradykinin and angiotensin III similar to those obtained with conventional ESI‐MS (Cahill et al, 2015). To improve the imaging performance of this method, a commercial optical microscope has been integrated into the vertically aligned LA‐LVC/ESI system to generate highly focused UV laser beam for laser ablation and provide bright‐field and fluorescence microscopy capabilities (Cahill, Kertesz, & Van Berkel, 2015).…”
Section: Laser Desorption/ablation Coupled To Ambient Ionization In Bioapplicationsmentioning
confidence: 99%
“…This arrangement typically results in greater particle collection efficiency by LA-LCE than by LA-EESI methods. There are several permutations of these approaches including LA-LVC [22,[132][133][134], LA-sample transfer [135][136][137], LA-solvent capture by aspiration [138,139], and ambient infrared laser ablation mass spectrometry (AIRLAB-MS) [140]. Unlike with LA-EESI approaches, analyte extraction is not particle size dependent in LA-LCE.…”
Section: Tissue Imagingmentioning
confidence: 99%